Understanding Evidence-Informed Decision-Making in a Community-Based Network Working Towards the Baby Friendly Initiative - Lukeman, Sionnach (Université d'Ottawa / University of Ottawa, 2013)
Objective: To understand the use of evidence-informed decision-making within an interorganizational network, and identify the facilitators and barriers to achieving network goals. Design: Case study. Setting: Rural health district in Nova Scotia, Canada (2006 to 2011). Participants: Members from 4 organizations representing community and hospital groups participating in a regional Baby Friendly Initiative network. Methods: A descriptive mixed methods study using focus group and questionnaire methodology. Data were analyzed using framework analysis and social network analysis (SNA). Results: The SNA results highlighted the role that relationships have on the sharing of knowledge among network members. The findings highlight the need for leadership at multiple levels (community, network members, primary organizations, and the provincial government). A lack of resources to achieve the network’s goals was a key barrier. Conclusions: The role of multi-level leadership is important for future network development and community consideration. The case study methodology facilitated momentum towards the network’s goals.
Keywords: Evidence-Informed Decision-Making; Baby Friendly Initiative; Social Network Analysis; mixed methods case study; case study; Interorganizational network; Canada; breastfeeding; network leadership